Hsa_circ_0003489 Drives PTX Resistance of Human NSCLC Cells Through Modulating miR-98-5p/IGF2 - Xia S; Wang C (Dove Medical Press, 2023)
Shaofeng Xia,1 Chenliang Wang2 1Department of Thoracic Surgery, The First People's Hospital of Jiujiang City, Jiujiang, Jiangxi, People's Republic of China; 2Department of Pathology, The First People's Hospital of Jiujiang City, Jiujiang, Jiangxi, People's Republic of ChinaCorrespondence: Chenliang Wang, Department of Pathology, The First People's Hospital of Jiujiang City, Jiujiang, Jiangxi, 332000, People's Republic of China, Tel +86- 13970298684, Email wangchenliang684@126.comBackground: Circular RNAs (circRNAs) demonstrated critical roles within developing tumors and treatment resistance in an increasing body of research. The aim was to look into the functions and processes of hsa_circ_0003489 in the non-small cell lung cancer (NSCLC) paclitaxel (PTX) resistance.Methods: NSCLC cell-based cultures including A549 and H460 were employed for such an investigation. hsa_circ_0003489, miR-98-5p, and insulin-like growth factor 2 (IGF2) expression-profiles were evaluated with a quantitative real-time polymerase chain reaction (RT-qPCR). The PTX resistance was determined using MTT assay, and the ELISA test measured IGF2 expression. Facilitating corroboration for miR-98-5p relation and hsa_circ_0003489 or IGF2, a dual-luciferase reporter method was applied.Results: The hsa_circ_0003489 level was raised in cells and tissues from PTX-resistant (PR) NSCLC. In PR NSCLC cells, hsa_circ_0003489 knockdown reduced PTX resistance. For the purpose of the mechanism study, hsa_circ_0003489 knockdown substantially reduced IGF2 expression via miR-98-5p sponging, improving PTX sensitivity in PR NSCLC.Conclusion: Through miR-98-5p/IGF2 axis control, hsa_circ_0003489 knockdown helped NSCLC overcome PTX resistance, suggesting a potential circRNA-targeted therapy for the disease.Keywords: Hsa_circ_0003489, PTX resistance, NSCLC, miR-98-5p, IGF2